Are Young Swimmers Short and Middle Distances Energy Cost Sex-Specific? - Massini, Danilo A.; Almeida, Tiago A. F.; Vasconcelos, Camila M. T.; Macedo, Anderson G.; Espada, Mário A. C.; Reis, Joana F.; Alves, Francisco J. B.; Fernandes, Ricardo J. P.; Pessôa Filho, Dalton M. (Frontiers in Physiology, 2021)
This study assessed the energy cost in swimming (C) during short and middle distances to analyze the sex-specific responses of C during supramaximal velocity and whether body composition account to the expected differences. Twenty-six swimmers (13 men and 13 women: 16.7 ± 1.9 vs. 15.5 ± 2.8 years old and 70.8 ± 10.6 vs. 55.9 ± 7.0 kg of weight) performed maximal front crawl swimming trials in 50, 100, and 200 m. The oxygen uptake (V˙O2) was analyzed along with the tests (and post-exercise) through a portable gas analyser connected to a respiratory snorkel. Blood samples were collected before and after exercise (at the 1st, 3rd, 5th, and 7th min) to determine blood lactate concentration [La–]. The lean mass of the trunk (LMTrunk), upper limb (LMUL), and lower limb (LMLL) was assessed using dual X-ray energy absorptiometry. Anaerobic energy demand was calculated from the phosphagen and glycolytic components, with the first corresponding to the fast component of the V˙O2 bi-exponential recovery phase and the second from the 2.72 ml × kg–1 equivalent for each 1.0 mmol × L–1 [La–] variation above the baseline value. The aerobic demand was obtained from the integral value of the V˙O2 vs. swimming time curve. The C was estimated by the rate between total energy releasing (in Joules) and swimming velocity. The sex effect on C for each swimming trial was verified by the two-way ANOVA (Bonferroni post hoc test) and the relationships between LMTrunk, LMUL, and LMLL to C were tested by Pearson coefficient. The C was higher for men than women in 50 (1.8 ± 0.3 vs. 1.3 ± 0.3 kJ × m–1), 100 (1.4 ± 0.1 vs. 1.0 ± 0.2 kJ × m–1), and 200 m (1.0 ± 0.2 vs. 0.8 ± 0.1 kJ × m–1) with p < 0.01 for all comparisons. In addition, C differed between distances for each sex (p < 0.01). The regional LMTrunk (26.5 ± 3.6 vs. 20.1 ± 2.6 kg), LMUL (6.8 ± 1.0 vs. 4.3 ± 0.8 kg), and LMLL (20.4 ± 2.6 vs. 13.6 ± 2.5 kg) for men vs. women were significantly correlated to C in 50 (R2adj = 0.73), 100 (R2adj = 0.61), and 200 m (R2adj = 0.60, p < 0.01). Therefore, the increase in C with distance is higher for men than women and is determined by the lean mass in trunk and upper and lower limbs independent of the differences in body composition between sexes.